Kajian Yuridis Sanksi Pidana Terhadap Ayah Sebagai Pelaku Tindak Pidana Pemerkosaan Menurut Qanun Nomor 6 Tahun 2014 - Liza Agnesta Krisna (Universitas Medan Area, 2016)
The purpose of this study was to determine the sanction of criminal law to the father as the perpetrator of rape according to Law No. 35 of 2014 on the Amendment of Act No. 23 of 2002 and Qanun No. 6 of 2014 on the Law Jinayat and analysis of Court Decision shar ' Yeah Langsa No. 05 / JN / 2016 / MS. The method used in this research is the analysis of the content or the content analysis, which uses secondary data research that is in-depth discussion of the content of a written document from the book and other scientific papers relevant to criminal law arrangements. But in this study also used the sociological method / empirical to do an interview to one Syar'iyah Court judges. The conclusion is that there is a difference writings criminal sanctions in Law No. 35 of 2014, with Qanun No. 6 of 2014. The criminal sanction in Qanun No. 6 of 2014 was lower than in Act No. 35 of 2014 which is the legal umbrella of safeguards against child.